National Survey of Pharmacist Awareness, Interest, and Readiness for Over-the-Counter Hearing Aids - Elizabeth S. Midey; Alexis Gaggini; Elaine Mormer; Lucas A. Berenbrok (MDPI AG, 2022)
Hearing loss is a major public health concern, affecting over 30 million Americans. Few adults who could benefit from hearing aids use them. Hearing aids are now available over-the-counter (OTC) for persons with perceived mild-to-moderate hearing loss. Community pharmacies will sell OTC hearing aids to increase public access to hearing healthcare. The purpose of this study was to describe pharmacist awareness, interest, and readiness to offer OTC hearing aids at community pharmacies. A multiple-item online survey was designed using the Theory of Planned Behavior and responses were collected from licensed pharmacists from July 2021 to December 2021. Descriptive statistics were used to summarize the 97 responses collected. Most respondents were not aware of the upcoming OTC hearing aid availability. Most respondents were somewhat or very interested in increasing their knowledge on OTC hearing aids, selling OTC hearing aids, and assisting patients with OTC hearing aid selection. Most respondents disagreed or strongly disagreed that they had the necessary knowledge to counsel patients on OTC hearing aids. The most reported supporting factor was training and educational resources. OTC hearing aids are a unique public health initiative which will expand patient access to hearing health care to community pharmacies.